Monetary de-measurement of taxation using cogni-economic pressure coefficient on a continuous progressivity model: Towards equitable taxation for Kenya - Stanley K. Kirika (Cogent Economics & Finance, 2020)
Tax derives from subjects' earnings measured in monetary terms, a principle anchored in financial accounting. The canon of equity, especially the vertical form, sometimes referred to as "ability to pay" remains monetary. However, negating conventional horizontal equity, equal taxable incomes often require employment of different economic rationality levels to earn them depending on the profession or sector the tax payer comes from; hence different cognitive energies are required to generate the same taxable income-disapproving the mere "ability to pay" paradigm. From the Gamma Rationality Measure for the credit unions sector that comprises 67% of Kenyan economic livelihoods and using a combination of econometric and Riemann double integral methods, the income consumption rationality function is derived, from which a Cogni-economic Pressure Coefficient is generated for each income level. The coefficient is used to work out a more equitable tax structure from a continuous progressivity tax model, for greater equity, incidentally securing a boost to productivity and economy canons of tax administration-a global lesson, specific for Kenya.
Keywords: 330; cogni-economic pressure coefficient; gamma rationality measure; income consumption rationality function; psych-social economic equation